ClotAssist: A program to treat cancer-associated thrombosis in an outpatient pharmacy setting. (June 2019) - Easaw, Jacob C; McCall, Susan; Azim, Adrian
Stable cancer patients diagnosed with a pulmonary embolus or deep vein thrombosis are commonly referred to the emergency department for management. This practice strains an already overburdened emergency department and is associated with long wait times and poor disease/injection education for patients. This pilot study sought to determine if stable cancer patients with newly diagnosed cancer-associated thrombosis could be effectively managed by community-based pharmacists who followed an evidence-based protocol to prescribe and initiate low-molecular weight heparin therapy. We hypothesized that this novel care pathway could provide faster patient care with more comprehensive disease education, self-injection training, and follow-up. Fifty-five patients with various cancers, including gastroesophageal, urogenital, breast, brain, and lung were enrolled into this pilot study. We observed that this alternative first-dose treatment pathway provided safe and effective treatment of venous thromboembolism combined with excellent patient satisfaction. Following their interaction with the pharmacist, patients felt confident about their ability to self-inject and about their venous thromboembolism management overall. No occurrences of bleeding or other side-effects were observed. This pilot study demonstrates that community-based pharmacists are capable of delivering complex care services in the outpatient environment, particularly in the management of venous thromboembolism.